2007
DOI: 10.1099/mic.0.2006/005181-0
|View full text |Cite
|
Sign up to set email alerts
|

The glgX gene product of Corynebacterium glutamicum is required for glycogen degradation and for fast adaptation to hyperosmotic stress

Abstract: Corynebacterium glutamicum cells growing in medium containing sugars accumulate glycogen in the early exponential-growth phase, and start to degrade this polymer at entry into the stationary phase. In a first attempt to investigate glycogen degradation, the C. glutamicum glgX gene, which encodes a protein with 46 % identity to the isoamylase-type debranching enzyme of Escherichia coli, was analysed, expressed and inactivated. The purified C. glutamicum gene product showed debranching activity towards glycogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…In Corynebacterium glutamicum, the exposure to hyperosmotic shock was shown to result in glycogen degradation and the synthesis of the osmoprotectant trehalose. 23 In C. elegans, recent reports demonstrate an important role for glycogen in mediating survival to hypoosmoticanoxic stress. 19,20 Our data suggest that glycogen degradation leads to different outcomes depending on the type of stress.…”
Section: The Glycogen Accumulation Conferred By Loss Of Flcn-1 Is Evomentioning
confidence: 99%
“…In Corynebacterium glutamicum, the exposure to hyperosmotic shock was shown to result in glycogen degradation and the synthesis of the osmoprotectant trehalose. 23 In C. elegans, recent reports demonstrate an important role for glycogen in mediating survival to hypoosmoticanoxic stress. 19,20 Our data suggest that glycogen degradation leads to different outcomes depending on the type of stress.…”
Section: The Glycogen Accumulation Conferred By Loss Of Flcn-1 Is Evomentioning
confidence: 99%
“…In contrast to the situation in E. coli, the genes for glycogen and maltose metabolism are not organized in operons in C. glutamicum and are not well distributed in the genome. Physiological studies also revealed that in C. glutamicum, glycogen synthesis and degradation have to be coordinated efficiently throughout cultivation since the glycogen level is set by the concerted action of glycogen-synthesizing and -degrading enzymes (43). The finding that activity of C. glutamicum MalP is controlled by competitive inhibition by the glycogen synthesis intermediate ADP-glucose is the first mechanism for the coordination of glycogen synthesis and degradation observed in C. glutamicum.…”
Section: Discussionmentioning
confidence: 95%
“…This mode of MalP activity control causes the fast degradation of glycogen in response to limitations of the glycogen synthesis. By this means, fluctuations of the central metabolism intermediates glucose-1-phosphate and glucose-6-phosphate are probably avoided, which reflects the proposed function of glycogen as a carbon capacitor in C. glutamicum (40,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations